Efektivitas sediaan spray ekstrak etanol Gracilaria sp. sebagai penolak nyamuk Aedes aegypti - Puspita, Wana; Pratami, Gina Dania; Setyaningrum, Endah; Nurcahyani, Nuning (Journal of Pharmaceutical and Sciences, 2025)
Dengue Hemorrhagic Fever or commonly known as DHF is a disease that is transmitted through the bite of female Aedes aegypti mosquitoes which carry the Dengue virus so that it can cause Extraordinary Events (KLB). Prevention of dengue fever is generally carried out using refills containing the chemical DEET (N,N-diethyl-meta-toluamide) which is dangerous for the skin. Gracilaria sp. It is known to contain compounds that are toxic to mosquitoes, such as alkaloids, flavonoids, steroids, saponins, tannins and triterpenoids. This research aims to see the effectiveness of the ethanol extract of Gracilaria sp. as a repellent for Ae. aegypti, Effective Concentration 50% (EC50), irritating effects, and physical properties of the ethanol extract spray preparation of Gracilaria sp. The research was carried out with methodology in accordance with the recommendations of the World Health Organization Pesticides Evaluation (WHOPES) using a Completely Randomized Design (RAL). The protective power provided by the ethanol extract of Gracilaria sp. analyzed using Oneway ANOVA, followed by the Least Significant Difference (LSD) test. Probit analysis was carried out to determine the effectiveness of the ethanol extract concentration of Gracilaria sp. as a repellent. The research results show that concentration levels of 5%, 10%, 15%, and 20% provide protective power capabilities of 14.40%, 31.81%, 47.76%, and 61.17% respectively with an EC50 value of 18.86%. The spray is homogeneous and does not cause skin irritation. Conclusion, spray preparations containing ethanol extract of Gracilaria sp. potential as a repellent for Ae. aegypti. Using this repellent can help reduce the risk of dengue fever which is transmitted by mosquitoes. Further research is needed on the effectiveness of Gracilaria sp. as a repellent with a concentration above 20% and an irritation test was carried out on > 10 probands for > 15 minutes by spraying the preparation repeatedly.